Cu/W/HZSM-5 for methane conversion to liquid hydrocarbons - Saidina Amin, Nor Aishah; Anggoro, Didi Dwi (Universiti Malaysia Sabah, 2003)
The direct conversion of natural gas, and in particular, the principal component, methane to useful products has been intensely studied over the past decades. ZSM-5 zeolite hasÂ been known to be a suitable catalyst for olefin oligomerization, but it is known to be a suitable catalyst for olefin oligomerization, but it is not resistant to high temperatures. In this work, HZSM-5 was modified with copper and tungsten to develop a highly active and heat resistant bifunctional oxidative-acid catalyst. The performances of Cu modified W/HZSM-5 were compared with HZSM-5 for the oxidation of methane to liquid hydrocarbons. The characterization results revealed that the addition of tungsten to HZSM-5 zeolite improved its thermal stability. Response Surface Methodology (RSM) was employed to determine the optimum methane conversion and C5+ selectivity. Numerical results indicated the optimum methane conversion of 29.54% with the corresponding C5+ selectivity of 57.2% were achieved at 12.3 vol % of O2, 203.9 ml/min of total feed flow rate, and % W doped of 3.2 wt%. The optimum C5+ selectivity of 70.2% was attained at 7.6 vol % of O2, 208.9 ml/min of total feed flow rate, and 3.2 wt% of W content with the corresponding methane conversion of 26.7%. By means of variance analysis and additional experiments, the adequacy of this model was confirmed.